ANALISIS PENGARUH KUALITAS SISTEM DAN KUALITAS LAYANAN SHARED SERVICES CENTER HUMAN CAPITAL DAN PROCUREMENT MELALUI DYNAMIC CAPABILITIES VIEW TERHADAP VALUE CREATION - Ikhwanoel Ikhwanoel; Anandha Budiantoro (Pusat Riset dan Inovasi Nasional, 2024)
This research was conducted to assess the value creation that can be obtained by companies by using the system quality and service quality of the Shared Services Center Human Capital and Procurement to support the company's business processes both financially and strategically, being able to separate the roles of supporting functions that have competence, capability and technical mastery high in assisting routine, repetitive and high-volume work processes as well as being effective and efficient in separating tactical and low-value tasks from strategic and higher-value tasks, so as to increase the company's dynamic capabilities view in implementing strategic management and capabilities organization to adapt to rapid and dynamic changes in the market environment and be able to provide services to internal and external customers in an end-to-end process, cost-effective, flexible and of high quality. Hypothesis testing in this research uses primary data by distributing questionnaires using non-probability sampling with a purposive sampling technique to 240 respondents from 5.298 all SSC Human Capital and Procurement service users using a Structural Equation Model approach based on Partial Least Square with the smartPLS version 3.0 program.